2018
DOI: 10.3389/fphar.2018.00790
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Challenges in the Clinical Translation of Nanoparticulate Nanomedicines: Pathways for Translational Development and Commercialization

Abstract: The use of nanotechnology in medicine has the potential to have a major impact on human health for the prevention, diagnosis, and treatment of diseases. One particular aspect of the nanomedicine field which has received a great deal of attention is the design and development of nanoparticulate nanomedicines (NNMs) for drug delivery (i.e., drug-containing nanoparticles). NNMs are intended to deliver drugs via various mechanisms: solubilization, passive targeting, active targeting, and triggered release. The NNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
477
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(478 citation statements)
references
References 100 publications
(233 reference statements)
0
477
0
1
Order By: Relevance
“…The main challenges related to the clinical translation are biological issues, safety, biocompatibility, intellectual property (IP), laws and regulations, and overall cost-effectiveness compared to traditional therapies [233], (Figure 3). These obstacles limit the usage of nanoparticles in the present markets regardless of their effectiveness [234]. Many issues should be considered during the clinical translation of nanomedicine.…”
Section: Challenges In the Clinical Translation Of Nanomedicinementioning
confidence: 99%
“…The main challenges related to the clinical translation are biological issues, safety, biocompatibility, intellectual property (IP), laws and regulations, and overall cost-effectiveness compared to traditional therapies [233], (Figure 3). These obstacles limit the usage of nanoparticles in the present markets regardless of their effectiveness [234]. Many issues should be considered during the clinical translation of nanomedicine.…”
Section: Challenges In the Clinical Translation Of Nanomedicinementioning
confidence: 99%
“…Even several formulations of liposomal and polymeric NPs earned the FDA‐approved and introduced in the market (Shi et al, ; Svenson, ). However, there are several key obstacles and challenges which are related to the clinical and translational development of targeted NPs in nanomedicine, such as lack of clear regulatory guidelines that are specific to targeted NPs, limited understanding of the biological stability of targeted NPs in human body and serum, and limited knowledge about NPs biocompatibility and biodegradability (Hua, De Matos, Metselaar, & Storm, ; Svenson, ). On the other hand, there is some incoordination between members of the investment community in conceptual understanding of the nanomedicine and scientific research recognize that has very low understanding about business expertise to develop commercial product in nanomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Material costs, also called 'external costs', is often a significant portion of capital required to run a trials-to-commercialization study 10,11,15,28,29 . It includes procurement, purification, manufacturing and packaging costs of a product along with any additional expenses incurred towards achieving regulatory approval and patenting 15,29 . In R&D, around 30% of the budget is spent on product development whereas the remainder is on clinical trials 8,9,11,12,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The material costs were 35 to 44% of the total capital for the three products identified for commercialization. However, it is difficult to compare these values with benchmarks from earlier studies as all material costs are factored into the final pricing of the material and end up in a clinical trial as "per-patient" or "per-site" costs 15,27,29,30 ; one study 15 reported that the 'clinical procedure costs' consumed about 22.32% of the overall costs. Most of the projects in this study procured materials either in bulk or small batches which made it easy for us to calculate material costs via invoicing.…”
Section: Discussionmentioning
confidence: 99%